Genetic uniformity, variety uniformity, and them effects on China's maize production - LI Hai-ming; ZHANG Shi-huang; HU Rui-fa (浙江大学学报. 农业与生命科学版)
Lack of diversity within a single crop species potentially limits the ability of species to respond to unknown or evolving pests, pathogens and environmental conditions, thus reduce the crop outputs. The coefficient of parentage (COP) is major indiex that is commonly adopted in agronomy and economy as a measure of genetic diversity. But different researches have obtained different results of correlation between genetic diversity and crop yield as indicated by COP. On this paper genetic uniformity, weighted coefficient of parentage, and variety uniformity of maize production in 20 provinces in China from 1982 to 1997 were calculated, and the effects of genetic diversity on maize production were studied using Production Function Model. Conclusions drawn by this study indicate that there is a significant negative correlation between genetic uniformity and maize yield; variety uniformity does not lead to genetic uniformity. Therefore, the government should make considerable investment in project of germplasm research in order to increase genetic diversity of maize in China.